ANALISIS RISIKO DAN PENGEMBALIAN DALAM INVESTASI SAHAM STUDI KASUS PADA SUB SEKTOR FOOD AND BEVERAGES DAN TABACCO MANUFACTURE PERIODE 2019-2022 - Apriani, Ely; Haeruddin, M. Ikhwan Maulana; Rauf, Anwar; Musa, Muhammad Ichwan; Amin, Andi Mustika (Transpublika Publisher, 2023)
This study aims to classify the value of shares that have high or low risk and return in stock investment in each company using the Capital Asset Pricing Model (CAPM) method so that it is easier for investors to make the right investment decisions in the Food and Beverages and Tabacco Manufacture sub-sectors. 2019-2022. The population in this research is shares in the Food and Beverages sub-sector and Tabacco Manufacture for the 2019-2022 period using a purposive sampling technique. Data collection techniques using documentation and literature study. The data analysis used in this study is data processing in the Microsoft Excel 2016 application program to classify investment decisions using the Capital Asset Pricing (CAPM) method. The results of the study show that the analysis of stock diversification using the Capital Asset Pricing Model shows that the food and beverages sub-sector has 20 samples and the Tabacco Manufacture sub-sector has 3 consistent stock samples during the 2019-2022 period. After analyzing the data, the results obtained in the Food and Beverages Sub Sector have 20 companies, there are 17 stocks that are classified as linear between risk and return, namely: AISA, ALTO, CEKA, CLEO, DLTA, GOOD, HOKI, ICBP, INDF, MLBI, MYOR, PSDN, BREAD, SKBM, SKLT, STTP, and ULTJ. Meanwhile, in the Tabacco Manufacture sub-sector, which has 3 companies, there are 2 stocks that are classified as linear between risk and return, namely: GGRM and RMBA.